Psychological Impact of β-Thalassemia Major in Young Patients - Ayesha Irshad; Abdul Sannan; Farhan Hassan; Ayesha Imran; Fatima Ehsan; Ghamza Gul; Janita Mushtaq; Laraib Sajawal; Madiha Qamar; Maham Ahmad (Students’ Supplement of Journal of Rawalpindi Medical College, 2022)
Abstract Background: ß-Thalassemia is an inherited blood disorder that shows a marked psychological burden in affected individuals. Objective: To explore the psychological implications of ß-Thalassemia major in young patients living in Rawalpindi and Islamabad. Materials and Methods: A study was conducted between March to November 2021 at the Thalassemia center of Holy Family Hospital, Rawalpindi. 306 voluntary patients suffering from ß-Thalassemia major on regular blood transfusion between the age of 10-30 years were included in the study through consecutive sampling. DASS-42 questionnaire was used. Semi-structured in-depth interviews were taken by the researchers to know the perception of patients about Thalassemia. Data were analyzed using SPSS version 21. Age, gender, and the effects of depression, anxiety and stress on routine activities, school performance and personalities were recorded. Results: Among the study participants 62% of β-Thalassemia patients were suffering from anxiety, 40% from depression and 41% individuals were facing having moderate stress as per DASS score. Mean scores SD of participants were 9.25(6.77) for depression, 9.32(4.02) for anxiety and 18.46(8.90) for stress. Mean depression, anxiety and stress scores were higher among 10-20 years old males; however, the difference was not statistically significant. Conclusion: β-Thalassemia has major psychological impacts on life of patients causing stress, anxiety and depression affecting them physically, mentally, and socially. Keywords: Quality of Life, depression, anxiety, Thalassemia major.